2015
DOI: 10.1007/s12630-015-0461-5
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid: When is enough (data) enough?

Abstract: Tranexamic acid (TXA) is a synthetic analog of the amino acid lysine which exerts its effect by binding with the lysine-binding sites on the plasminogen molecule. It reversibly and competitively reduces the affinity of plasminogen binding with fibrin, decreases the activation of plasminogen to plasmin, and reduces the local degradation of fibrin by plasmin. Since its development in the early 1960s, TXA has been proven to be a remarkably effective drug in reducing perioperative blood loss and therefore the requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Given the pharmacological action of TXA, there are concerns about the routine use of TXA in THA and the risk of inducing a hypercoagulatory state with an increased risk of venous thromboembolism (either deep venous thrombosis or pulmonary embolism) and possibly other cardiovascular outcomes such as myocardial infarction or ischemic stroke 10,11 . However, we are not aware of any study that has shown perioperative TXA to be associated with an increased risk of thromboembolic events 12,13 .…”
Section: Galley Page 3 Of 17mentioning
confidence: 98%
“…Given the pharmacological action of TXA, there are concerns about the routine use of TXA in THA and the risk of inducing a hypercoagulatory state with an increased risk of venous thromboembolism (either deep venous thrombosis or pulmonary embolism) and possibly other cardiovascular outcomes such as myocardial infarction or ischemic stroke 10,11 . However, we are not aware of any study that has shown perioperative TXA to be associated with an increased risk of thromboembolic events 12,13 .…”
Section: Galley Page 3 Of 17mentioning
confidence: 98%
“…A compelling body of literature has established the efficacy of tranexamic acid (TXA) for transfusion reduction in total joint arthroplasty (TJA) . However, the previously reported use of TXA (11‐46% of TJA patients) belies the published evidence of drug efficacy, possibly due to unsettled questions of drug safety .…”
mentioning
confidence: 99%
“…A number of other studies propose that patients' conditions should be assessed prior to administration of Tranexamic acid in trauma-related hemorrhages. Thromboelastography is a method of evaluation prior to Tranexamic acid use (38)(39)(40)(41)(42)(43).…”
Section: Advances In Bioscience and Clinical Medicinementioning
confidence: 99%